Pepper pseudocaryophyllus (Myrtaceae): An integrative review - Sousa, Annalyvia Pastor; Silva, Emanuel Wendel de Queiroz; Oliveira, José Diógenes Silva; Amaral , Wanderlei do; Deschamps , Cicero; Silva, Luiz Everson da; Araújo, Jenifer Priscila de; Gonçalves , José Walber Castro; Colares, Aracélio Viana (Seven Editora, 2024)
The Pimenta pseudocaryophyllus (Gomes) Landrum among the species of the genus Mytaceae is the only Brazilian representative. Craveiro-do-mato, as it is popularly known in the Southern Region of Brazil, is an aromatic tree species, with popular use for medicines, condiments, and flavoring of beverages due to its flavor very similar to cloves. The Brazilian species has been widely used in traditional medicine for the treatment of various ailments, in addition to being linked to other traditional practices, such as the use of wood for internal carpentry works. However, there are not enough studies on its potential through biological activity. This study highlighted the botanical characteristics as well as the importance of expanding research regarding the chemical and biological activities of the species Pimenta pseudocaryophyllus (Gomes) Landrum. DOI:https://doi.org/10.56238/sevened2023.001-003